2022
DOI: 10.1111/anec.12980
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings in pregnant women in Angola

Abstract: Pregnancy is a physiological state characterized by adaptive changes that guarantee the adequate means for fetal development (Sanghavi & Rutherford, 2014). The cardiovascular (CDV) system undergoes progressive changes during pregnancy, resulting in hemodynamic changes characteristic of that period. The main changes involve increased blood volume, cardiac output, and decreased systemic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(63 reference statements)
2
1
0
Order By: Relevance
“…In this study, the HR increased obviously during the late pregnancy in horses, similar to earlier reports in pregnant Warmblood mares [ 37 ], humans [ 1 , 3 , 38 , 39 ] and in dogs [ 12 , 15 , 40 ]. In horses, the breed differences may reflect in maternal HR; the small-size mares had the highest HR compared to the medium-sized and large-sized mares [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, the HR increased obviously during the late pregnancy in horses, similar to earlier reports in pregnant Warmblood mares [ 37 ], humans [ 1 , 3 , 38 , 39 ] and in dogs [ 12 , 15 , 40 ]. In horses, the breed differences may reflect in maternal HR; the small-size mares had the highest HR compared to the medium-sized and large-sized mares [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…A cardiovascular function could be changed for physiological adaptation during pregnancy, including increases in heart rate (HR) [1], cardiac output (CO) [2], and a decrease in maternal systemic vascular resistance associated with the renin-angiotensin-aldosterone system activation [3]. The changes in cardiovascular function associated with pregnancy are relevant to clinical practice because they may be exacerbated in association with cardiovascular diseases, including hypertension [4,5], diabetes mellitus [6], and congenital heart disease [7] and also lead to the development of pre-eclampsia in women [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found reduced PR interval in pregnant women without cardiac disease. 27,28 This may be a consequence of accelerated AV-node conduction due to factors such as increased sympathetic tone and increased heart rate during pregnancy Our findings were consistent with that.…”
Section: Discussionsupporting
confidence: 91%